Comparison of Thoracic Radiography and Computed Tomography in Calves with Naturally Occurring Respiratory Disease - Fowler, Jennifer; Stieger-Vanegas, Susanne M.; Vanegas, Jorge A.; Bobe, Gerd; Poulsen, Keith P. (Frontiers in Veterinary Science, 2017)
Objective: To evaluate the severity and extent of lung disease using thoracic computational radiography (CR) compared to contrast-enhanced multidetector computed tomography (MDCT) of the thorax in calves with naturally occurring respiratory disease and to evaluate the feasibility and safety of performing contrast-enhanced thoracic multidetector MDCT examinations in sedated calves. Furthermore, to evaluate if combining CR or MDCT with respiratory scoring factors will improve prediction of the chronicity of pulmonary disease in calves. Animals: Thirty Jersey heifer calves ranging in age between 25 to 89 days with naturally occurring respiratory disease. Procedures: All calves were evaluated via thoracic CR and contrast-enhanced MDCT. All calves were euthanized immediately following thoracic MDCT and submitted for necropsy. Imaging and histopathology results were compared with each other. Results: Thoracic MDCT was superior for evaluation of pneumonia in calves due to the lack of summation in all areas of the lungs. Intravenously administered sedation provided an adequate plane of sedation for acquiring MDCT images of diagnostic quality, without the need for re-scanning. A diagnosis of pneumonia was made with equal rate on both thoracic CR and MDCT. Although mild differences in classification of lung pattern and extent of lung disease were seen when comparing an experienced and a less experienced evaluator, the overall differences were not statistically significant. The best intra- and inter-observer agreement was noted when evaluating the cranioventral aspects of the lungs in either modality. Clinical respiratory scoring is inadequate for diagnosing chronicity of pneumonia in calves with naturally occurring pneumonia. Conclusion and clinical importance: Both imaging modalities allowed diagnosis of pneumonia in calves. The cranial ventral aspects of the lungs were most commonly affected. Thoracic CR and MDCT provided similar diagnostic effectiveness in diagnosing pneumonia. However, MDCT provided better assessment of subtle details, which may be otherwise obscured due to summation artifact.